2018
DOI: 10.1002/jmv.25337
|View full text |Cite
|
Sign up to set email alerts
|

Oroxylin A inhibits Kaposi's sarcoma‐associated herpes virus (KSHV) vIL‐6–mediated lymphatic reprogramming of vascular endothelial cells through modulating PPARγ/Prox1 axis

Abstract: Background and purpose Kaposi's sarcoma–associated herpes virus (KSHV) vIL‐6 is sufficient to induce lymphatic reprogramming of vascular endothelial cells, which is a key event in Kaposi's sarcoma (KS) development. This study was aimed to investigate the effect of Chinese herb oroxylin A on lymphatic reprogramming and neovascularization by KSHV vIL‐6 in vitro and in vivo. Methods The lymphatic‐phenotype endothelial cell line was generated by lentiviral KSHV vIL‐6 infection. Cell viability and apoptosis were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Apparently, OA regulates the expression of multiple proteins, such as transforming growth factor beta (TGF-β), nuclear factor E2-related factor 2 (Nrf2), mitofusin 2 (Mfn2), angiopoietin 2 (Ang-2), vascular endothelial growth factor (VEGF), glutathione (GSH), B-cell lymphoma 2 (Bcl-2), Bcl-2-associated X protein (Bax), caspase -3, -8 and -9, sirtuin 3 (SIRT3), alpha-smooth muscle actin (α-SMA), etc., [ 75 , 76 , 77 , 78 , 79 ]. The proteomic screening of cancer cells treated with OA has revealed that it downregulates several factors, such as mitochondrial uncoupling protein 2 (UCP2), MMP-2, MMP-9, PKM2, superoxide dismutase 2 (SOD2), hypoxia inducible factor 1 alpha (HIF-1α), and PROX1 [ 62 , 80 , 81 ].…”
Section: Molecular Targets Of Oamentioning
confidence: 99%
“…Apparently, OA regulates the expression of multiple proteins, such as transforming growth factor beta (TGF-β), nuclear factor E2-related factor 2 (Nrf2), mitofusin 2 (Mfn2), angiopoietin 2 (Ang-2), vascular endothelial growth factor (VEGF), glutathione (GSH), B-cell lymphoma 2 (Bcl-2), Bcl-2-associated X protein (Bax), caspase -3, -8 and -9, sirtuin 3 (SIRT3), alpha-smooth muscle actin (α-SMA), etc., [ 75 , 76 , 77 , 78 , 79 ]. The proteomic screening of cancer cells treated with OA has revealed that it downregulates several factors, such as mitochondrial uncoupling protein 2 (UCP2), MMP-2, MMP-9, PKM2, superoxide dismutase 2 (SOD2), hypoxia inducible factor 1 alpha (HIF-1α), and PROX1 [ 62 , 80 , 81 ].…”
Section: Molecular Targets Of Oamentioning
confidence: 99%
“…Other therapies and their respective therapeutic targets in signaling pathways modulated by KSHV oncoproteins, such as vIL-6 [128], have been described. Oroxylin A inhibits vIL-6-mediated lymphatic reprogramming of vascular endothelial cells through modulating PPARγ/Prox1 axis.…”
Section: Challenges Of Current Ks Therapies and Potential Kshv Viral ...mentioning
confidence: 99%
“…Oroxylin A inhibits vIL-6-mediated lymphatic reprogramming of vascular endothelial cells through modulating PPARγ/Prox1 axis. Thus, this therapy may serve as a candidate for the treatment of KS [128].…”
Section: Challenges Of Current Ks Therapies and Potential Kshv Viral ...mentioning
confidence: 99%
“…Specifically, PPARG counter-regulated 12 molecules that were upregulated or downregulated by LSCC ( Figure 2). The expression levels of eight LSCC markers (XIAP, UBE2D1, SKP2, ACKR3, MI21, HOXA10, STAT1, and PDPN) were significantly upregulated in LSCC patients [13][14][15][16][17][18][19][20] and were downregulated by PPARG [21][22][23][24][25][26][27][28]. On the other hand, PPARG could activate multiple genes [29][30][31][32][33] inhibited by LSCC [34][35][36][37][38], including MIR 223, PTEN, ANGPT1, CYP2A6, and FOXA2.…”
Section: Ppar Researchmentioning
confidence: 99%